2020
DOI: 10.1159/000513689
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Duodenal Ulcer: Strategies in High-Risk Ulcers

Abstract: <b><i>Background:</i></b> Acute peptic ulcer bleeding is still a major reason for hospital admission. Especially the management of bleeding duodenal ulcers needs a structured therapeutic approach due to the higher morbidity and mortality compared to gastric ulcers. Patient with these bleeding ulcers are often in a high-risk situation, which requires multidisciplinary treatment. <b><i>Summary:</i></b> This review provides a structured approach to modern management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…A sufficient level of albumin is important for enhancing the wound healing of ulcers 42,43 . Alternatively, prophylactic TAE after initially successful hemostasis can be a promising treatment modality in cases with a very high rebleeding risk, 44 e.g. PBDU with serum albumin <2.5 g/dL.…”
Section: Discussionmentioning
confidence: 99%
“…A sufficient level of albumin is important for enhancing the wound healing of ulcers 42,43 . Alternatively, prophylactic TAE after initially successful hemostasis can be a promising treatment modality in cases with a very high rebleeding risk, 44 e.g. PBDU with serum albumin <2.5 g/dL.…”
Section: Discussionmentioning
confidence: 99%
“…However, when analyzing the frequency of repeated bleeding, it was shown that TAE may be associated with an increase in the frequency of repeated bleeding compared to surgery. It is important to understand that further decisions regarding the treatment of patients after unsuccessful endoscopy should be made in a multidisciplinary manner (collectively by an endoscopist, surgeon, and radiologist), taking into account the individual condition of the patient (age and concomitant pathologies) and the features of bleeding (Mille et al, 2021). It was identified that the presence of a history of gastroduodenal ulcer is an independent risk factor when assessing the need for endoscopic intervention among patients with bleeding in the upper gastrointestinal tract (in addition to the assessment according to the Glasgow-Blatchford prognostic criteria for bleeding risk and the urea-creatinine nitrogen scale) (Takatori et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In one study, the concentrations of various cytokines were studied in patients with duodenal ulcers complicated by bleeding Figure 2 (Mille et al, 2021). It is known that the presence of H. pylori triggers local and systemic cytokine signaling, which, in turn, can affect healing and carcinogenesis processes, as well as possible perforation.…”
Section: Resultsmentioning
confidence: 99%
“…Another reason is that it is sometimes difficult to control bleeding of the main trunk of the GDA by hemoclipping or thermocoagulation, even with an over-the-scope clip. [ 1 , 10 , 11 ] Thanks to advances in catheters and embolization materials, an increasing number of studies have concluded that angiography and embolization techniques are safe and effective and can be used as alternatives to surgery, especially for patients who cannot tolerate surgery. [ 1 ] It is worth noting that there is a rare complication of embolization coil migration.…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the special location of the duodenum and poor visual field after bleeding, endoscopic therapy still faces a great challenge, especially in patients with active bleeding ulcers, large ulcers (size > 1.5 cm), and ulcers with large-sized nonbleeding vessels (diameter > 2 mm), who have a high risk of rebleeding after endoscopic therapy. [ 1 ] Transcatheter arterial embolization (TAE) is recommended when endoscopic hemostasis fails owing to its minimal invasiveness and effectiveness. In recent years, some studies have suggested that prophylactic transcatheter arterial embolization can reduce the risk of rebleeding in patients with a high risk of endoscopic treatment failure.…”
Section: Introductionmentioning
confidence: 99%